Penerapan Model PBL dalam Meningkatkan Hasil Belajar Siswa Kelas VI SD Inpres Minasa Upa - Hidayat, Muhammad Rachmat; Hasmiani; Bahri, Aliem (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research is a classroom action research (PTK) which aims to find out the process of applying the Problem Based Learning model on the material of the arrival of foreign nations in Indonesia in class VI and to find out the improvement of learning outcomes on the material of the arrival of foreign nations in Indonesia with the application of the Problem Based Learning learning model. The approach used in this research is a qualitative approach. The data collection techniques used were observation, tests and documentation. The research subjects were teachers and students, totaling 1 teacher and 20 students. The research was conducted in two cycles. In cycle I, the results of research on the learning process from the teacher's aspect were in good qualifications (B) with a percentage of 86.66%, from the student's aspect were in sufficient qualifications (C) with a percentage of 70% and the learning test results were in sufficient qualifications (C) with an average score of 66. Whereas in cycle II the results of research on the learning process from the teacher aspect were in good qualifications (B) with a percentage of 93.33%, from the student aspect were in good qualifications (B) with a percentage of 95.33% and the learning outcomes test was in good qualifications (B) with with an average score of 80.